Anti-inflammatory effects and molecular mechanisms of bioactive small molecule garlic polysaccharide - Shao, Xin; Li, Jialong; Zhang, Huidan; Zhang, Xuhui; Sun, Chongzhen; Ouyang, Xin; Wang, Yong; Wu, Xiyang; Chen, Chunbo (Frontiers in Nutrition, 2023)
Although garlic polysaccharides have been found to possess anti-inflammatory activities, anti-inflammatory study on small molecule water-soluble garlic polysaccharide (WSGP) is few. In this study, a novel WSGP with a molecular weight of 1853 Da was isolated by DEAE-52 and Sephadex G-100 column and the chemical composition was identified by monosaccharide composition and methylation analysis. Furthermore, the antioxidant effects of WSGP and the potential molecular mechanisms on LPS-induced inflammatory responses in RAW264.7 macrophage cells were investigated. The results showed that WSGP has strong antioxidant activity, such as DPPH, hydroxyl, superoxide anion, ABTS radical scavenging capacity, Fe2+ chelating ability and reducing power. Meanwhile, WSGP could considerably suppress the manufacturing of NO and the mRNA and protein expression degrees of IL-6, TNF-α, and IL-1β in LPS inspired RAW264.7 macrophages WSGP could significantly suppress the production of NO and the mRNA and protein expression levels of IL-1β, IL-6, and TNF-α in LPS stimulated RAW264.7 macrophage cells (p < 0.05). In addition, the phosphorylated IκB-α, p65, and STAT3 proteins were significantly increased in LPS-induced macrophages, while this trend was significantly reversed by WSGP treatment in a concentration-dependent manner (p < 0.05). Consequently, WSGP supplementation might reduce LPS-induced inflammatory responses by suppressing proinflammatory cytokines and NF-κB and STAT3 pathway activation. The finding of this research would give scientific guidelines for the judicious use of small molecular garlic polysaccharide in anti-inflammatory treatments.